Lightning breakdown voltages of refined bleached and deodorised palm oil under needle-plane configuration - Azis, Norhafiz; Thien, Yee Von; Yunus, Robiah; Yaakub, Zaini (Universiti Putra Malaysia Press, 2017)
In recent years, vegetable oil such as Palm Oil (PO) has been identified as a potential alternative dielectric insulating fluid for transformers. It is biodegradable, non-toxic and has high flash and fire points. In this paper, a study on the positive lightning impulse breakdown voltages of PO under non-uniform field is carried out. The testing was carried out using needle-plane electrodes configuration at gap distances of 25 mm and 50 mm. Rising voltage, 1 and 3 shots per step testing methods were used and 3 types of Refined Bleach and Deodorized Palm Oil (RBDPO) and Mineral Oil (MO) were examined. It was found there is no significant effect on the breakdown voltages of all samples. The breakdown voltages of all RBDPO at 50% probability are comparable with MO. At 1% probability and gap distance of 50 mm, the breakdown voltages of all RBDPO are lower than MO.